Analisa Pengaruh Kesiapan Karayawan Terhadap Penerimaan Modul Manajemen Pelatihan Pada PT XYZ - Pandia, Vinra (AI Society & STMIK Indonesia, 2024)
A Learning Management System (LMS) is a critical system designed to electronically manage content, training, and employee performance. An LMS allows companies to systematically manage and evaluate training programs and provide users with easy access to training content. However, many LMS implementations fail due to a lack of attention to user readiness when adopting new technology. This study aims to analyze the influence of user readiness (self-efficacy, individual innovativeness, self-directed learning, and motivation) on the acceptance of LMS-based training modules at PT XYZ. The research uses the Technology Acceptance Model (TAM) framework and the Partial Least Square Structural Equation Modelling (PLS-SEM) method for 69 respondents. The results show that self-efficacy, self-directed learning, and motivation significantly affect the perceived ease of use of the training modules. Meanwhile, motivation significantly affects the perceived benefits of the training modules. The research findings are expected to help plan to improve employee readiness before LMS implementation to promote the acceptance and success of technology-based training systems.